Development and optimisation of hepatitis B recombinant antigen loaded chitosan nanoparticles as an adjuvant using the response surface methodology. (1st September 2020) - Mehrabi, Mohsen; Sadeghi‐Soureh, Shima; Mohammadpour Dounighi, Naser; Rezayat, Seyed Mahdi; Doroud, Delaram; Khoobi, Mehdi; Amani, Amir
Abstract : The main purpose of this Letter was to develop and optimise recombinant hepatitis B antigen‐loaded chitosan nanoparticles (rHBsAg‐CS NPs) as a new adjuvant for hepatitis B vaccine through designing by response surface methodology (RSM). The NPs were prepared by employing ionic gelation technique. RSM was utilised by selecting the independent variablesincluding the concentration of CS, tripolyphosphate and antigen concentration as well as pH and homogenisation speed to obtain maximum encapsulation efficiency (EE) and loading capacity (LC). EE and LC of the optimised preparation were 93.2 ± 1.1 and 25.6 ± 1.38%, respectively. Optimised NPs showed spherical shape, particle size of 187 ± 14 nm and positive zeta potential (+31.3 ± 1.5 mV). In vitro release profile of optimised formulation revealed an initial burst, followed by a slow sustained antigen release. Cell viability assay indicated that the toxicity of NPs was concentration‐dependent. SDS‐PAGE analysis confirmed the structural stability and integrity of the released antigen. ELISA and Ouchterlony double immunodiffusion tests of released antigen showed that the antigenicity was preserved during the process of NP formation.